Lithiated polymer coating for interface stabilization in Li6PS5Cl-based solid-state batteries with high-nickel NCM - Shi, Bing-Xuan; Weber, Franjo; Yusim, Yuriy; Demuth, Thomas; Vettori, Kilian; Münchinger, Andreas; Titvinidze, Giorgi; Volz, Kerstin; Henss, Anja; Berger, Rüdiger; Richter, Felix H.; Justus Liebig University Giessen (My University, 2025)
Li6PS5Cl-based solid-state batteries with high-nickel LiNi0.9Mn0.05Co0.05O2 (NCM) promise higher energy density and safety than lithium-ion batteries with liquid electrolyte. However, their cycling performance is often limited by interface degradation between NCM and solid electrolyte. Here, a sulfonated polyphenylene sulfone/polyvinylpyrrolidone (sPPSLi/PVP) coating on NCM particles is presented that mitigates this issue. This uniform coating impedes direct contact between NCM and solid electrolyte, which lessens interface degradation and improves cycling performance. Electrochemical impedance spectroscopy and chronoamperometry show a reduced interface resistance and Li+-ion transport length during cycling for sPPSLi/PVP-coated NCM in Li6PS5Cl-based solid-state batteries. Additionally, the coating effectively suppresses side reactions, particularly the formation of oxygenated species, at the NCM/SE interface. Overall, sPPSLi/PVP-coated NCM shows remarkable improvements in cycling stability and rate capability, emphasizing the significance of applying polymer coatings.
Keywords: ddc:540